Seleksi Beasiswa Untuk Perguruan Tinggi Berdasarkan Pendekatan Keputusan Berkeadilan dengan Fuzzy Mamdani - Amsar Amsar; Rizal Munadi; Ramzi Adriman (LPPM Politeknik Aceh Selatan, 2017)
The scholarship is one of the funding schemes of study in an education system. Various models and names of scholarship schemes are offered on terms that have been determined by the scholarship provider. The essence of these conditions is the trust and confidence of the funders of the scholarship recipients and is projected to complete the study period as per the allocated funds. In general, funders are very concerned about the issue of academic qualification as one of the main indicators. However, for prospective students who wish to pursue higher education from coming from orphaned families and from less financially qualified families, with good academic qualifications, not yet a parameter in the selection process of scholarship recipients. Based on this fact, this problem would like to find solution in this research and submitted the selection model of scholarship with fair decision approach. This study aims to design a fair decision-making system as a tool for selection of scholarship recipients that prioritize the values ​​of justice by prioritizing scholarship recipients from among orphans and poor. This research proposes two methods: Fuzzy Mamdani and weighting method, with 4 input parameters which are used as variables: children status and economic level, residence condition, children achievement and family dependent. Simulation testing performed by considering the parameters set is a more effective and efficient decision model for the prospective scholarship recipients. To obtain a competent recipient, then the screening process by ranking to be declared passed the selection and received as the recipient of scholarship in accordance with the number of quotas provided. This selection model becomes an alternative and provides opportunities for orphans and the poor to continue higher education and improve the human resource index as well as meet national education goals.